PHOTOBOOK DESIGN FOR CHINESE RELIGIOUS TOURIST PLACES IN BATAM CITY - Zulkarnain Zulkarnain; Welvin Hendrison (Universitas Internasional Batam, 2022)
Batam City is one of the islands in the Riau Archipelago province with a strategic location. Besides being on an international shipping route, Batam island is also close neighbors to Singapore and Malaysia, which can make a distinct advantage for this island with many foreign tourists who come for vacation, worship and also to know the history of various objects in Batam City, namely Religious tourism related to religion with there are various pagodas, monasteries, and statues that are the main attraction. The design of this photobook is used to promote and also introduce various religious tourism objects in Batam City to local and foreign people by providing some information such as locations, facilities, and also the history of the religious tourism objects. For the development of the collected images, the Adobe Photoshop CS6 application will be used. The research method used is observation and documentation. The final result of this research is to make a Photobook that will be printed with a size of 20 x 20 cm which contains the location, buildings, and also existing facilities of the various religious tourism objects with the aim of increasing visitor interest and adding insight to local and foreign communities. about the history of religious tourism in Batam City.